Combination of smartphone digital image colorimetry and UV-Vis spectrophotometry as detection systems with solidified floating organic drop microextraction as preconcentration method for the quantification of methyl red in wastewater samples - Bombom, Miray; Girgin, Ayca; Zaman, Buse Tugba; Turak, Fatma; Bakirdere, Sezgin (Tubitak Scientific & Technological Research Council Turkey, 2023)
In this study, a portable smartphone-based digital image colorimetric system (SDIC) was designed and integrated with a solidified floating organic drop microextraction method (SFODME) for the quantification of methyl red in textile wastewater samples. The RGB (red, green, and blue) data were evaluated for each captured image, and the green channel was selected for quantification due to its linear response for the analyte. Under optimal conditions, an acceptable linear range was recorded for the analyte. The proposed method recorded a limit of detection (LOD) value of 0.046 mg/L. The developed microextraction method was also combined with UVVis spectrophotometry, which recorded an LOD value of 0.012 mg/L. Real sample analysis was carried out with textile wastewater samples to check the applicability/accuracy of the developed method, using a matrix matching calibration strategy to enhance quantification accuracy. Satisfactory percent recoveries in the range of 93.3%-114.3% and 92%-92.7% were recorded for the SFODME-SDIC and SFODME-UV methods, respectively.
Keywords: Methyl red; smartphone digital image colorimetry; UV-Vis spectrophotometry; solidified floating organic drop microextraction; textile wastewater; LIQUID-PHASE MICROEXTRACTION; RESPONSE-SURFACE METHODOLOGY; BOX-BEHNKEN DESIGN; SEAWATER SAMPLES; EXTRACTION; Chemistry; Engineering